The Influence of Effective Communication and Information Technology on Maritime Literacy in the Digital Era Which Impact Participant Satisfaction at the Imare Training Centre for Seafarers (Jakarta Maritime Imare) - Aziz, Muhammad Mughni; Irham, Muhammad; Malau, April Gunawan (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the influence of effective communication and information technology on digital-era maritime literacy and its impact on the satisfaction of training participants at the IMARE Training Center for Seafarers (IMARE Maritim Jakarta). Maritime literacy in the context of the digital era is a crucial aspect in supporting the transformation of seafarers' competencies amidst the rapid development of global shipping information systems and technology. This research adopts a quantitative approach with a cross-sectional design. The population consists of all training participants from January to December 2024, totaling 2,708 participants, spanning various training programs such as CMT, CMHBT, SAT, SDSD, SSO, MC, MFA, and IMDG. The sample was determined using the Slovin formula, resulting in 349 respondents selected through proportional random sampling. Data were collected via questionnaire distribution and analyzed using the latest version of SmartPLS software. The findings indicate that effective communication and information technology have a positive and significant influence on maritime literacy, and that maritime literacy positively affects the satisfaction of training participants. Additionally, both communication and information technology show a significant indirect influence on satisfaction through maritime literacy. These findings highlight the vital role of two-way communication and the use of training technology in enhancing the quality of education and participant satisfaction in seafarer training in the digital age